Applications and usability of interactive TV : 5th Iberoamerican conference, jAUTI 2016, La Habana, Cuba, November 21-25, 2016, revised selected papers /: 5th Iberoamerican conference, jAUTI 2016, La Habana, Cuba, November 21-25, 2016, revised selected papers. (2019) - Unknown
No abstract available